Cyclodextrin-induced host–guest effects of classically prepared poly(NIPAM) bearing azo-dye end groups - Maatz, Gero; Maciollek, Arkadius; Ritter, Helmut (Beilstein Journal of Organic Chemistry, 2012)
A thermo-, pH- and cyclodextrin- (CD) responsive poly(N-isopropylacrylamide) (PNIPAM), with a N,N-dimethylaminoazobenzene end group was synthesized. Using 3-mercaptopropionic acid as a chain transfer agent, PNIPAM with a well-defined COOH end group was obtained. The acid end group was transferred to the corresponding acid chloride and then functionalized with N,N-dimethyl[4-(4’-aminophenylazo)phenyl]amine. This dye-end-group-labeled polymer showed acidochromic effects, depending on the pH and the presence of randomly methylated β-cyclodextrin (RAMEB-CD). Also higher cloud-point values for the lower critical solution temperature (LCST) in the presence of RAMEB-CD were observed. Additionally, this azo-dye-end-group-labeled polymer was complexed with hyperbranched polyglycerol (HPG) decorated with β-CD to generate hedgehog-like superstructures.
Keywords: azo-dye; cyclodextrins; end-group functionalization; host–guest interaction; supramolecular aggregation